2017
DOI: 10.1089/zeb.2016.1377
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Diversity and Evolutionary Trends in Armored Catfish Species of the Genus Harttia (Siluriformes: Loricariidae)

Abstract: Most species of the genus Harttia inhabits the headwaters of small tributaries, but some species are restricted to the main channel of some rivers. This feature, combined with limited dispersal ability, leads to the formation of small isolated populations with reduced gene flow. Currently, there are 23 taxonomically defined and recognized species, and 17 of these are found in Brazil, distributed in several hydrographic basins. Despite this diversity, few chromosomal data for the species belonging to this genus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…Despite such great species diversity, cytogenetic studies are available for only eight of them, all from Brazilian Southern regions, with exception for Harttia punctata [ 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, although still limited, the chromosome data are already enough to notice a conspicuous variation of the diploid number (2n) in the genus, ranging from 2n = 52♀/53♂ in H. carvalhoi [ 8 ] to 2n = 62♀♂ in H. absaberi [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite such great species diversity, cytogenetic studies are available for only eight of them, all from Brazilian Southern regions, with exception for Harttia punctata [ 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, although still limited, the chromosome data are already enough to notice a conspicuous variation of the diploid number (2n) in the genus, ranging from 2n = 52♀/53♂ in H. carvalhoi [ 8 ] to 2n = 62♀♂ in H. absaberi [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, although still limited, the chromosome data are already enough to notice a conspicuous variation of the diploid number (2n) in the genus, ranging from 2n = 52♀/53♂ in H. carvalhoi [ 8 ] to 2n = 62♀♂ in H. absaberi [ 9 ]. Chromosomal breaks and rearrangements as Robertsonian fusions, fissions, as well inversions were proposed to occur in the karyotype diversification of Harttia species [ 13 ]. In addition, two multiple XY-derived sex chromosome systems were also identified: ♀XX/♂XY 1 Y 2 in H. carvalhoi [ 8 ] and ♀X 1 X 1 X 2 X 2 /♂X 1 X 2 Y in H. punctata [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harttia is a genus of the subfamily Loricariinae that has 26 valid species (Fricke et al, 2019). Of these, only eight species present cytogenetic data (Alves et al, 2003;Kavalco et al, 2005;Centofante et al, 2006;Rodrigues, 2010;Blanco et al, 2012aBlanco et al, , 2013Blanco et al, , 2014Blanco et al, , 2017. The genus Harttia has conspicuous karyotype diversity, with diploid numbers (2n) ranging from 52 chromosomes in Harttia carvalhoi Miranda Ribeiro, 1939 females (Centofante et al, 2006) to 62 chromosomes in Harttia absaberi Oyakawa, Fichberg & Langeani, 2013 (cited as Harttia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome variability at the intra-and interspecific level are detected in comparative cytogenetic studies [16][17][18] . In addition, recent cytogenetic data showed that evolutionary breakpoint regions clustered in repetitive DNA regions promoted genomic reshuffle and chromosome evolution in Loricariidae species [19][20][21][22][23][24][25] . Iguaçu River is an important tributary of Paraná River basin in the south region of Brazil and presents high endemism of its ichthyofauna due to the isolation caused by the formation of the Iguaçu waterfalls 22 Mya ago 26 .…”
Section: Introductionmentioning
confidence: 99%